Suppression of Concentration Quenching in Ortho‐Substituted Thermally Activated Delayed Fluorescence Emitters. Issue 2 (4th December 2019) - Abroshan, Hadi; Cho, Eunkyung; Coropceanu, Veaceslav; Brédas, Jean‐Luc
Abstract: Thermally activated delayed fluorescence (TADF) emitters are typically embedded at low concentrations in a host matrix to suppress emission quenching. However, recent studies indicate that TADF compounds such as the oBFCzTrz emitter (5‐(2‐(4, 6‐diphenyl‐1, 3, 5‐triazin‐2‐yl)phenyl)‐5H‐benzofuro[3, 2‐c]carbazole) display insignificant concentration quenching dependence. To understand the origin of this beneficial behavior, the morphology, dynamics, electronic properties, and charge transport and energy transfer in a neat film of the oBFCzTrz emitter are characterized via molecular dynamic simulations combined with density functional theory calculations. The emissive layer shows glassy behavior at room temperature with the twisted configurations of the emitter molecules allowing for intramolecular donor–acceptor interactions, but disfavoring intermolecular π–π stacking, which suppresses the formation of intermolecular aggregate states. As a result, the electronic structure and luminescence of oBFCzTrz are not significantly altered by intermolecular interactions. The calculated diffusion lengths of the singlet and triplet excitons are small enough that there occurs no substantial concentration quenching effect. Overall, the design of new TADF emitters with structural motifs similar to those of oBFCzTrz offers potential to develop efficient organic light‐emitting diode devices in which the emissive layers are entirely composed of TADF molecules without the need for a host component. Abstract : The origin of limited concentration quenching in ortho‐substituted thermally activated delayed fluorescence emitters is studied via a multipronged computational approach. The twisted configurations of the emitter molecules disfavor intermolecular π–π stacking, which results in their luminescence being not significantly altered by molecular interactions. The rates of excitation energy transfer are very small, making exciton–exciton annihilations unlikely.